2004
DOI: 10.1103/physrevb.70.235411
|View full text |Cite
|
Sign up to set email alerts
|

Probe effect in scanning tunneling microscopy onSi(001)low-temperature phases

Abstract: The probe effect, the effect of parameters in scanning tunneling microscopy (STM) measurement, on the Si͑100͒ surface with two competing phases in delicate balance, was investigated systematically by reexamining its influence on the Si͑100͒ dimer flip-flop motions at 5 and 80 K. On the basis of the results, the complex array of the phenomena of the Si͑100͒ surface structures was comprehended. The phase transition between c͑4 ϫ 2͒ and p͑2 ϫ 2͒ structures below ϳ40 K was studied by STM, as well as by low-energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…Another factor that may affect STM measurements is a tip-surface interaction. Such a probe effect previously has been reported on the Si(100) surface [17,18]. We found that the obtained images to a large extent depended on what kind of atoms on the apex of the STM tip.…”
Section: Methodsmentioning
confidence: 49%
“…Another factor that may affect STM measurements is a tip-surface interaction. Such a probe effect previously has been reported on the Si(100) surface [17,18]. We found that the obtained images to a large extent depended on what kind of atoms on the apex of the STM tip.…”
Section: Methodsmentioning
confidence: 49%
“…The phase transformation between c(4 Â 2) and p(2 Â 2) structures on the Si(0 0 1) substrates at low temperatures under STM observation has been reported [32,[42][43][44]. Our theoretical investigation [45] shows that the torque applied by the additional surface electric field on the Si(0 0 1) substrates induced by STM causes the transformation.…”
Section: Model Potential For the Dimer Systemmentioning
confidence: 67%
“…In this regard, the Bi nanolines represent a very intriguing system, since their electronic properties could be altered by simply changing the reconstruction of the Si background, which could be triggered by temperature changes [25], manipulated by a scanning probe tip [30][31][32], or by hydrogenation, as demonstrated by our simulations above. Bi nanolines themselves are very stable against changes in temperature (up to 750 K), whereas the Si surface is very sensitive, and experiences a phase transition from p(2 × 2) to c(4 × 2) at low temperatures.…”
Section: B Scanning Tunneling Microscopy Featuresmentioning
confidence: 79%